Gastric cancer nodal tumour–stroma ratios influence prognosis. Issue 13 (14th October 2020) - Huang, J.; Yang, B.; Tan, J.; Zhou, S.; Chen, Z.; Zhong, G.; Gao, H.; Zhu, J.; Zeng, J.; Zhong, L.; Liu, X.; Han, F.
Abstract : This study showed that nodal tumour–stroma ratio (NTSR) is an independent prognostic factor for overall and disease‐free survival of patients with gastric cancer. Both relative stroma‐rich primary tumour–stroma ratio (PTSR) and NTSR were independent negative prognostic factors for overall survival in gastric cancer. This study supports assessment of tumour–stroma ratio in the routine pathological diagnosis of gastric cancer. validated in node‐positive disease